2018
DOI: 10.1002/mrm.27529
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of vascular properties derived from ultrafast DCE‐MRI to discriminate malignant and benign breast tumors

Abstract: Purpose We propose a novel methodology to integrate morphological and functional information of tumor‐associated vessels to assist in the diagnosis of suspicious breast lesions. Theory and Methods Ultrafast, fast, and high spatial resolution DCE‐MRI data were acquired on 15 patients with suspicious breast lesions. Segmentation of the vasculature from the surrounding tissue was performed by applying a Hessian filter to the enhanced image to generate a map of the probability for each voxel to belong to a vessel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…At a lower field strength, one has to compromise on using either a high temporal resolution suitable for PK analysis or a high spatial resolution for detailed morphologic assessment. Our findings are in good agreement with prior studies at 1.5 and 3T, which demonstrated the potential of PK parameters to aid in the differentiation of benign from malignant tumors [ 14 , 18 , 32 , 44 , 45 , 46 , 47 ]. We integrated the information from quantitative PK analysis to established reporting guidelines, i.e., BI-RADS, showing that PK-enhanced BI-RADS improved diagnostic accuracy from 88.4% to 97.7% by reducing false-positive findings.…”
Section: Discussionsupporting
confidence: 91%
“…At a lower field strength, one has to compromise on using either a high temporal resolution suitable for PK analysis or a high spatial resolution for detailed morphologic assessment. Our findings are in good agreement with prior studies at 1.5 and 3T, which demonstrated the potential of PK parameters to aid in the differentiation of benign from malignant tumors [ 14 , 18 , 32 , 44 , 45 , 46 , 47 ]. We integrated the information from quantitative PK analysis to established reporting guidelines, i.e., BI-RADS, showing that PK-enhanced BI-RADS improved diagnostic accuracy from 88.4% to 97.7% by reducing false-positive findings.…”
Section: Discussionsupporting
confidence: 91%
“…In the earlier studies, the presence of vessels adjacent to breast cancer or an increase in the number of vessels in the cancer‐bearing breast are said to be associated with a poor prognosis . A recent study suggested that the diagnostic ability of breast MRI could be improved by knowing the number of vessels associated with lesions using both UF‐DCE MRI and high‐resolution CE MRI . Combined evaluation of the number of vessels and AVI may further increase the diagnostic accuracy of breast MRI.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce systematic errors in the model fits, the AIF was calibrated for each DCE-MRI scan to segmented skeletal muscle tissue [ 76 ] prior to fitting for pharmacokinetic parameters. Additionally, each tumor voxel time-course was fit to a half-logistic function to determine the bolus arrival-time, which was used to shift the calibrated AIF on a voxel-wise basis to align the enhancement time of C p ( t ) with the bolus arrival-time [ 77 ]. Voxel-wise fits to the standard Kety-Tofts model were bound within the physiological range for each parameter (e.g., 0 to 5 min −1 for K trans , 0 to 1 for v e ).…”
Section: Methodsmentioning
confidence: 99%